Inovasi Singkong SnacKarang untuk Penguatan UMKM dan Ekonomi Desa Petahunan - Chicha Aprilia Fahruridho; Luayyi’ Dewi Mariyam; Hovivah Hovivah; Saiti Mu’awana; Ramzy Aranzha Revy; Miftahul Maghfiroh; Hendra Kurniawan; Eleonora Angelina; Via Lailatur Rizki; Yessy Anggraeni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
Cassava is a tuber crop that can easily be found in community land, especially in rural areas. Petahunan village has abundant cassava agricultural products but its utilization is still limited to traditional products with low economic. Community Service through Real Work Lecture (KKN) from Institute Technology and Business Widya Gama Lumajang aims to improve the skills and economic independence of village communities through innovation of processed products made from cassava. The program is carried out with an integrated training approach that includes the provision of tools and materials as well as direct practice in making processed products. The target of this activity is housewives and micro-entrepreneurs who have high enthusiasm in developing local businesses. Innovation is focused on making a snack product called Snackarang, which is a snack made from cassava that is processed by grating it lengthwise, frying it until crispy and seasoned with a combination of spicy and sweet flavors. The results of the activity showed that participants were able to produce snacks that have high appeal and better selling value compared to previous products. This activity succeeded in opening new opportunities, increasing community creativity in processing local agricultural products and strengthening the village's economic potential through the development of value-added products.